2023
DOI: 10.3389/fbioe.2023.1118850
|View full text |Cite
|
Sign up to set email alerts
|

Sustained intra-articular reactive oxygen species scavenging and alleviation of osteoarthritis by biocompatible amino-modified tantalum nanoparticles

Abstract: Recent studies highlight the vital role of oxidative stress and reactive oxygen species (ROS) during progression of osteoarthritis (OA). Attenuating oxidative stress and reducing reactive oxygen species generation in joints represent reasonable strategies for the treatment of osteoarthritis. To address the potential question for clinical translation, and improve the biocompatibility and long-term performance of current antioxidants, the present study provided high biocompatible small positively charged tantalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Sagittal and coronal plane images from rat knee joint CT scans were utilized to evaluate the presence of osteophytes and signs of osteoporosis in OA. Furthermore, an analysis of bone volume to total volume (BV/TV) and trabecular thickness was conducted to further assess the bone health ( Jiang et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sagittal and coronal plane images from rat knee joint CT scans were utilized to evaluate the presence of osteophytes and signs of osteoporosis in OA. Furthermore, an analysis of bone volume to total volume (BV/TV) and trabecular thickness was conducted to further assess the bone health ( Jiang et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we performed lunate and scaphoid bone replacement with 3D printed tantalum, which we believed was the first attempt in the world. During the follow-ups, we found that patients had great improvement in grip strength and wrist movement after surgery, indicating that tantalum has good biocompatibility ( Jiang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of metal implants such as Ti, [19,20] Ti particles can cause Mϕ M1 polarization and enhance osteoclast activity, thereby inducing bone resorption and accelerating the corrosion of the Ti itself. In the study of Ta particles on Mϕ polarization, existing literature suggests that Mϕ can polarize toward the M2 phenotype on surfaces of Ti-Ta composites with 20% Ta; [21] boronized Ta coatings reduce Mϕ inflammatory response and promote osteogenic matrix secretion in bone marrow-derived mesenchymal stem cells (BMSCs); [22] Ta nanoparticles scavenge reactive oxygen, suppress inflammatory factor secretion, [23,24] and increase the polarization of M2 Mϕ and decrease the Mϕ polarization to the M1 phenotype under the inflammatory microenvironment. [25] Thus, clarifying how Ta particles regulate Mϕ M2 polarization and the associated mechanisms is crucial for understanding their mediation effects in bone formation and resorption processes.…”
Section: Introductionmentioning
confidence: 99%